La percepción no conceptual en el cine etnográfico de jorge prelorán (Argentina, 1960/1970) - Campo, Javier Alberto (2017)
The prominent figure in Argentine ethnographic film has long been Jorge Prelorán. He is the filmmaker who has perhaps most thoroughly reflected on his practice. Prelorán defined in his work and writings what he meant by ethnographic film: neither ethnography nor cinema, but rather both at once. Neither science nor art, but located in the middle of the magnetic field that both areas radiate. He made about fifty ethnographic documentaries in Argentina. Prelorán built his career on the idea that all images that can be combined to make a film are part of this infinite bank of things that can be called "the universe." If the world of film images is independent, to say they are "created" as a "representation" is impertinent. Under this conception, the subject is no longer the center; therefore, he is not entirely in control of his creation. Gilles Deleuze understood this quite well in his revolutionizing contributions to film studies. Movement-image film is action and reaction, a constant updating of the operation of a sensory-motor mechanism. In the development of these problematic issues through the films of the Argentine filmmaker, I will discuss principles that movie studios have considered as revealed truths, including the concept of authorship.